Antibacterial, anticancer, anti-diabetic and catalytic activity of bio-conjugated metal nanoparticles. (25th July 2018) - Patra, Nabanita; Kar, Dattatreya; Pal, Abhisek; Behera, Anindita
Abstract: Improvement of biological activities of medicinal plant in combination with metal nanoparticles is highly appealing. Herein, bio-conjugated AuNP and AgNP have been synthesized at room temperature using leaf extract of Saraca asoca a medicinal plant. Phytochemicals present in aqueous leaf extract of Saraca asoca, are acting as reducing, capping and stabilizing agent. The formation of nanoparticles is confirmed and characterized by different instrumental techniques like UV-visible and IR spectroscopy, SEM, TEM and XRD analysis. Both nanoparticles are spherical, monodisperse and crystalline in nature. Phytochemicals, comprising of functional groups like aliphatic ester C–O–C, alcoholic and phenolic–OH in extract are responsible for reduction of metal precursor and functional groups like N–H or O–H are responsible for capping and stabilization of nanoparticles. Preliminary biological activities like antibacterial, anticancer and anti-diabetic activity of bio-conjugated metal nanoparticles are screened through disc diffusion methods, MTT assay and α -amylase inhibition assay. Both AuNP and AgNP show antibacterial activity (zone inhibition values 9.6 mm and 9.7 mm for E. coli and 7.7 mm and 11 mm for B. subtilis, respectively) and anti-diabetic activity (IC50 1.5 mM and 0.35 mM, respectively) whereas AgNP displays growth inhibition of prostate cancer cell line . CAM assay confirm the biocompatibility of synthesized nanoparticles. Further, both nanoparticles show excellent catalytic activity towards the reduction of 4-nitrophenol (4-NP) using as reducing agent even at very low concentration.